Job creation and job destruction over the life cycle: the older workers in the spotlight - Jean-Olivier Hairault; Arnaud Chéron; François Langot (Institute for the Study of Labor (IZA), 2007)
This paper extends the job creation - job destruction approach to the labor market to take into account the life-cycle of workers. Forward looking decisions about hiring and firing depend on the time over which to recoup adjustment costs. The equilibrium is typically featured by increasing (decreasing) firing (hiring) rates with age, and a hump-shaped age-dynamics of employment. The empirical plausibility of the model is assessed by incorporating existing age-specific labor market policies in France. Finally we show that the age-dynamics of employment is optimal when the Hosios condition holds and we design the optimal age-pattern for employment policies when this condition does not apply
urn:nbn:de:101:1-20080422232
Keywords: 330; Arbeitsuche; Arbeitsnachfrage; Arbeitsplatzsicherung; Altersgruppe; Erwerbsverlauf; Arbeitsmarktpolitik; Frankreich